LncRNA LGALS8-AS1 Promotes Breast Cancer Metastasis Through miR-125b-5p/SOX12 Feedback Regulatory Network - Zhai, Duanyang; Li, Tianfu; Ye, Runyi; Bi, Jiong; Kuang, Xiaying; Shi, Yawei; Shao, Nan; Lin, Ying (Frontiers in Oncology, 2021)
Background: Metastasis is a major factor weaking the long-term survival of breast cancer. An increasing evidence revealed that long non-coding RNAs (lncRNAs) are involved in the occurrence and development of breast cancer. In this study, we aimed to investigate the role of LGALS8-AS1 in the metastasis progression in breast cancer cells and its potential mechanisms. Results: Here, we showed that lncRNA LGALS8-AS1 was highly expressed in breast cancer and associated with poor survival. LGALS8-AS1 functioned as an oncogenic LncRNA that promoted metastasis of breast cancer both in vitro and in vivo. Mechanistically, LGALS8-AS1 upregulated Sex determining region Y-box 12 (SOX12) via competing as a ceRNA for sponging miR-125b-5p, and acted the PI3K/AKT signaling pathway to promote the metastasis of breast cancer. Furthermore, SOX12 in turn activated LGALS8-AS1 expression via direct recognition of its sequence binding enrichment (SBE) motif on the LGALS8-AS1 promoter, thereby forming a positive feedback regulatory loop. Conclusion: This study manifested a novel mechanism that LGALS8-AS1 facilitated the metastasis of breast cancer through a potential ceRNA regulatory pathway and might be a potential target for therapeutical applicable in clinic.